2010
DOI: 10.1109/tvcg.2010.157
|View full text |Cite
|
Sign up to set email alerts
|

FI3D: Direct-Touch Interaction for the Exploration of 3D Scientific Visualization Spaces

Abstract: Abstract-We present the design and evaluation of FI3D, a direct-touch data exploration technique for 3D visualization spaces. The exploration of three-dimensional data is core to many tasks and domains involving scientific visualizations. Thus, effective data navigation techniques are essential to enable comprehension, understanding, and analysis of the information space. While evidence exists that touch can provide higher-bandwidth input, somesthetic information that is valuable when interacting with virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 44 publications
(67 reference statements)
1
23
0
Order By: Relevance
“…For example, Cohé et al's tBox [11], Reismann et al's 3D-RST [56], and Yu et al's FI3D [87] provide dataset navigation facilities, Fu et al's powers-of-10 ladder [19] provides scale navigation at different levels, and Yu et al [85,86] suggest context-aware spatial selection techniques.…”
Section: Tactile Input and Its Use For 3d Data Explorationmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Cohé et al's tBox [11], Reismann et al's 3D-RST [56], and Yu et al's FI3D [87] provide dataset navigation facilities, Fu et al's powers-of-10 ladder [19] provides scale navigation at different levels, and Yu et al [85,86] suggest context-aware spatial selection techniques.…”
Section: Tactile Input and Its Use For 3d Data Explorationmentioning
confidence: 99%
“…For example, even though Coffey et al's Slice WIM widgets [10] were demonstrated in their video in a bimanual fashion, the widget could also be used with several fingers of the same hand and we thus classify it as unimanual interaction. In contrast, while Yu et al's FI3D [87] can be used in a unimanual fashion, their constrained interaction modes necessarily require bimanual input due to the widget's design.…”
Section: Interaction Tasks In Spatial 3d Data Visualizationmentioning
confidence: 99%
See 3 more Smart Citations